Cholinergic stimulation with pyridostigmine, hemodynamic and echocardiographic analysis in healthy subjects - Pontes,Paulo Vasconcellos de (1999)
OBJECTIVE: Growing evidence suggests that sudden death after an acute myocardial infarction (AMI) correlates with autonomic nervous system imbalance. Parasympathomimetic drugs have been tested to reverse these changes. However, their effects on ventricular function need specific evaluation. Our objective was to analyze pyridostigmine's (PYR) effect on hemodynamic and echocardiographic variables of ventricular function. METHODS: Twenty healthy volunteers underwent Doppler echocardiographic evaluations, blood pressure (BP), and heart rate (HR) assessment at rest, before and 120 min after ingestion of 30 mg PYR or placebo, according to a double-blind, placebo-controlled, crossed and randomized protocol, on different days. RESULTS: PYR was well tolerated and did not cause alterations in BP or in ventricular systolic function. A reduction in HR of 10.9±1.3% occurred (p<0,00001). There was an A wave reduction in the mitral flow (p<0.01) and an E/A ratio increase (p<0.001) without changes in the other diastolic function parameters (p>0.05). CONCLUSION: PYR reduces HR and increases E/A ratio, without hemodynamic impairment or ventricular function change.